Tratamento do superendividamento do consumidor à luz da Lei n° 14.181/2021: contribuições sociais e econômicas do novo modelo jurídico - GONÇALVES, Clayrtha Raissa Nascimento (2023)
The overindebtedness of customers is the phenomenon that includes those people who have more debts in relation to their payment capacity. The law n. 14.181/2021 (July 1st, 2021) regulates the prevention and the treatment of overindebtedness. This research discusses the application of this law about how it can contribute to the treatment of overindebtedness. The hypothesis is about the recognition of economical and social relevance of referred treatment, analyzing the possible practical consequences of its application. The research is organized in relation to the general objective to analyze critically the treatment of consumer overindebtedness obtained by recent law, measuring the possible social and economical impacts in the construction of new judicial paradigms. Specific objectives, in Contemporary Private Law area, achieving relevant considerations to the construction of decision legal pattern; describing the inherent and encircling characters about the consumer overindebtedness; and analyzing the possibility of economical and social impacts of consumer legislation of treatment of the overindebtedness. The basic theory is Miguel Reales ́s (1994) pattern, which contributes to construction of new legal patterns, including the decision model issued by judges; this is added to the view of legal consequentialism of Ricardo Lorenzetti (2009). Methodologically, we can choose qualitative research, with reasoning of intuitive kind, to use particular data from pilot projects and theories to infer a general truth wider than funded premises. As a procedure method, we used the monographical method. As a generic kind of investigation of applied social sciences to legal science, we use the legal, descriptive and propositive researches. Based on critical, social and legal analysis; the techniques of bibliographical research and documentary one are chosen by the author. The practical aim of the research is to highlight a way of contribution to the reality, to help in the solution of conflicts by Judiciary in the light of consumer overindebtedness treatment institute.